A Grammatical and Semantic Non-equivalence Analysis of Cinderella Text Translation - Hapni Nurliana H.D Hasibuan (Journal of English Language Teaching, Linguistics, and Literature Studies, 2021)
A grammatical and semantic non-equivalence analysis of Cinderella text translation. Research paper: This research’s aims to determine the grammatical non-equivalence in the translation of English and Indonesian in Cinderella texts. This research is based on Baker's theory of grammatical equivalence (1992) and Nida & Taber's about semantic equivalence (1982). The research method used is a mixed method (quantitative-qualitative). Quantitative methods are used to classify grammatical and semantic incompatibility categories while the qualitative methods are on the content analysis approach. The finding showed that Cinderella text has non-equivalence translation in Grammatical such: number, persona, gender, and tense and semantic is lost meaning and the meaning changes.Keywords: translation, grammatical equivalence, semantic equivalence, short story,Cinderella